2016
DOI: 10.17265/1537-1506/2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Analyze Small and Medium Enterprises’ Training Needs Related to the Internationalization

Abstract: Formal training can play a particularly important role in supporting the internationalization of small and medium enterprises (SMEs). However, the demand for education services by the latter still appears limited. This is due to known structural and cultural limits that are found widely in this type of business and to the fact that the provision of training-especially that which is funded-does not seem to address adequately SMEs' needs; in many cases, such training is not stimulating, because it is perceived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Narver and Slater (1990), for example, found that market orientation has a significant impact on firm profitability, increasing market growth in the long term. This finding has been emphasized by subsequent studies that found a direct relationship between IMO and SMEs’ international expansion into new markets (Nakos et al ., 2019; Pascucci et al ., 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Narver and Slater (1990), for example, found that market orientation has a significant impact on firm profitability, increasing market growth in the long term. This finding has been emphasized by subsequent studies that found a direct relationship between IMO and SMEs’ international expansion into new markets (Nakos et al ., 2019; Pascucci et al ., 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These capabilities can be leveraged in diverse ways to enhance IMO’s impact on business performance (Olavarrieta and Friedmann, 2008). In contrast, SMEs constrained by limited financial resources and lacking experience in foreign markets, face heightened risk and uncertainty in international expansion (Hollender et al ., 2017; Nakos et al ., 2019; Pascucci et al ., 2016). Despite the crucial role of IMO in mitigating these challenges for SMEs, the literature reveals a scarcity of studies exploring the relationship between IMO and international performance in the SME context, with disparate findings and a lack of consensus among existing studies (Acosta et al ., 2018; Fernandes et al ., 2020; Kolbe et al ., 2022; Pascucci et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation